The evaluation of anchoring processes and chemical stability of zwitterionic molecules via local reactivity indexes - Gomes, O. P. [UNESP]; Batagin-Neto, A. [UNESP]; Lisboa-Filho, P. N. [UNESP] (Elsevier, 2021)
Exposure of materials to blood can result in numerous interactions such as plasma protein adsorption, blood cell activation, platelet adhesion, and thrombotic reactions. Although strategies to minimize the blood-immune response with the coating surface of these biomaterials are being developed, many of the specific factors that trigger this immune response are still unknown. Among the approaches to overcome this situation, the surface modification by zwitterionic molecules is promising due to their recognized biocompatibility and anti-fouling properties. Here we present a computational study on the structural, electronic, and reactivity properties of a series of anti-fouling zwitterionic molecules containing sulfobetaine, carboxybetaine and phosphorylcholine groups with distinct anchoring segments. Details on the adsorption and anchoring of these molecules on SiO2 model systems as well as their interaction with water molecules were investigated. The results indicate that the evaluation of local softness matching can bring valuable information regarding the anchoring processes and stability of zwitterionic molecules. In addition, it is shown that the analysis of the frontier levels of the compound's components defines an effective and cheap approach for the proposition and identification of new/improved systems.
Keywords: Biomaterials; Molecular modelling; Surface modification; Zwitterionic molecules